(untitled) (European journal of volunteering and community-based projects, 2021)
Increasingly, organisations occupy an intermediate position between public and private ownership; such organisations are called hybrid organisations (Doherty et al., 2014), whose goal is to create innovation and synergy in addressing complex social issues, leading to more sustainable development (Karré, 2020). In the paper, we investigate how the actions of hybrid organisations produce public value, adopting a conceptual scheme that relates broad strategic objectives of general (and public) interest to the policies that public administrations put in place. The objective is to plan and report on the sustainability and social impact dimensions of hybrid organisations, information that is central to the public sector entity, whose principal and specific role is to provide quality services to the target community. The hybrid organisation must account for its social performance, report on it and draw up an action plan to improve its performance. Therefore, it is a process through which public administration can better understand the impact of its actions on the community and, consequently, be accountable to its primary stakeholders. In this paper, we address the research question of how value creation is accounted for in hybrid organisations. Several approaches for reviewing the scientific stream can be applied in the management sector. For example, bibliometric reviews use a qualiquantitative approach to evaluate and monitor published research, considering statistics on authors, journals and countries (Zupic & Čater, 2015). According to Massaro et al., (2016), in bibliographic and bibliometric analysis, researchers may be interested in representing a static picture, providing answers about the history of the research field under investigation, and using bibliographic pairing of authors, keywords and citations. In our analysis, the composition of the research field was set: only products from the subject area 'Business, Management & Accounting'. Following the studies by Mariani & Borghi, (2019), Massaro et al., (2016) and Secinaro et al., (2020), only "articles" written in the "English" language were considered. Following studies Li et al., 2017; Xu et al., (2018), articles published in journals on the ABS list (2018) with the classification at 1, 2, 3, 4 and 4* were considered. This choice is widely adopted in bibliometric studies, and researchers commonly employ it to identify quality scientific articles. We have also carefully reviewed the selected papers, highlighting those aspects that are useful for research and considering only those papers that have been published in journals in the relevant subject area. To perform the biometric analysis, we used the Bibliometrix application: a statistical package available on R-Studio (Aria & Cuccurullo, 2017); the software allows the representation of bibliometric information, including authors, citations, countries of production and keywords and Structured literature review.